2005
DOI: 10.1128/jvi.79.12.7431-7437.2005
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of the B5 Receptor for Herpes Simplex Virus Contains a Functional Region Important for Infection

Abstract: . 79:7419-7430, 2005). Heptad repeats found in the B5 C terminus are predicted to form an ␣-helix for coiled coil structure. We used mutagenesis and synthetic peptides with wild-type and mutant sequences to examine the function of the heptad repeat motif in HSV binding and entry into porcine cells that express B5 and for infection of naturally susceptible human HEp-2 cells. B5 with point mutations predicted to disrupt the putative C-terminal coiled coil failed to mediate HSV binding and entry into porcine cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Point mutations predicted to break the ␣-helix in the C terminus of B5 result in proteins that do not support HSV entry (24). This indicates an important function of the Cterminal region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Point mutations predicted to break the ␣-helix in the C terminus of B5 result in proteins that do not support HSV entry (24). This indicates an important function of the Cterminal region.…”
Section: Discussionmentioning
confidence: 98%
“…On the basis of analogies with viral entry or cell fusion proteins (5,13,16,17,28,31), we hypothesize that the predicted B5 C-terminal coiled coil may engage those found in an essential HSV glycoprotein or possibly in an as-yet-unknown accessory cellular protein. Computer-based analyses of HSV glycoprotein sequences show that only gH and gL contain heptad repeats with predicted high scoring ␣-helices (24). gH and gL are essential for HSV entry and cell fusion (2, 10, 29).…”
Section: Discussionmentioning
confidence: 99%
“…Recently a new HSV entry receptor was described (196); it is effectively blocked by binding of an ␣-helical peptide in a coiled-coil formation (197). Whether this receptor is specific for HSV-1 or also allows HSV-2 entry is unknown; therefore, this cannot definitively explain differences in the antiviral effects of peptides on the two viruses.…”
Section: Mode Of Action Of Antiviral Peptidesmentioning
confidence: 94%
“…Computational analysis showed that the C-terminus (amino acids 344-374) of B5 has a high probability of forming an a-helical coiled coil (7)(8)(9). This is particularly interesting, since computational modeling has also shown that it is highly possible that gH and gL form coiled coils (8)(9)(10).…”
Section: Introductionmentioning
confidence: 97%